Security study of WiMAX systems - Chia, Woanlan. (2010)
Denial of Service (DoS) is one of the most common attacks on wireless networks. Studies were done to research on the vulnerabilities and the security measures of IEEE802.16e against this type of attack. However, most of the researches were done through theory proving. This method however is less convincing as there maybe differences between theoretical and physical implementation. This report proposes to formally verify the Denial of Service (DoS) attack due to the vulnerabilities in the initial ranging protocol as specified in IEEE 802.16e. Two models are implemented in SPIN and the verification results are compared and analysed. The results shows that a DoS attack is possible based on the assumptions made during the modelling process. In addition, through simulation in SPIN, it was proven that encryption can be used for added security to prevent DoS.